Fatores associados à leptospirose em equinos de contingente militar no estado do Rio Grande do Sul - Bastiani, Mariane Pacheco (2020)
Leptospirosis is one of the most widespread zoonoses in the world; especially in developing countries representing a public health problem. The etiological agent, the bacteria Leptospira can infect a wide variety of species, which can act as reservoirs and / or renal carriers when chronically infected, excreting the bacteria through the urine. Leptospirosis in horses is usually asymptomatic and may be associated with recurrent uveitis, abortion, stillbirth and neonatal infection. The objectives of this study were to determine the occurrence of Leptospira spp. and to verify the factors associated to leptospirosis in horses from a military contingent of the state of Rio Grande do Sul. A total of 446 horses were evaluated and categorized into 309 mares (with an abortion history), 11 stallions, and 126 horses with an average age of 3 years. The microscopic serum agglutination technique was used to determine the seroprevalence of the population, and questionnaires were implemented to investigate the main factors linked to the infection present at the site to which the animals were exposed. The occurrence of anti-Leptospira spp. agglutinins was 54.48% (243/446) in the studied population. In the horses with an average age of 3 years, mares, and stallions the occurrence was 57.94% (73/126), 54.05% (165/309), and 45.45% (5/11), respectively. In all categories, the predominant serovar was Ballum followed by Icterohaemorrhagiae; however, in the stallions, the second most prevalent serovar was Tarassovi. The main ambiance factors were contact with different water sources, presence of rodents, and contact with wild and domestic animals. The high occurrence of anti-Leptospira spp. antibodies may be associated with the presence of these main factors. Therefore, the exposure of horses to possible reservoirs of Leptospira spp. should be minimized. Moreover, the immunoprophylaxis protocol should be reviewed and a shorter interval between vaccinations should be adopted to control leptospirosis, whose economic impact should be evaluated in horse populations.